Peran Lembaga Pendidikan MTs Ma’arif NU Toruakat di Kabupaten Bolaang Mongondow Dalam Pembentukan Karakter Religius Siswa - Latifa Anggol; Burhanudin A.K. Mantau; Firman Sidik (Pekerti: Journal Pendidikan Islam dan Budi Pekerti, 2025)
This study aims to describe strategic steps in fostering students' religious character at MTs Ma’arif NU Toruakat, a school located in Toruakat Village, Dumoga Sub-district, Bolaang Mongondow Regency, North Sulawesi Province. This is deemed important considering the geographical location, which is characterized by a high diversity of ethnicities, tribes, groups, and religions. The research employs a qualitative approach with a phenomenological method to uncover the social realities present in the field. The findings reveal that MTs Ma’arif NU Toruakat implements several measures, including creating a religious environment. This is achieved by applying a knowledge framework based on Ahlus Sunnah wal Jamaah to establish a solid foundation in religious understanding, requiring students to memorize the 30th chapter (juz) of the Quran to strengthen their connection with it, and implementing the Quran Reading, Writing, and Memorization Program (BTHQ). Supporting factors for these programs include the presence of highly qualified teachers, both in their religious character and teaching capabilities. Meanwhile, the inhibiting factor is the lack of adequate facilities and infrastructure at the school.